Pengaruh Pemahaman Akuntansi, Sistem Informasi Akuntansi, Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan (Studi Pada UMKM Bidang Kuliner di Kota Bandung) - Pratama, Egy; Kusumawardani, Astrin; Herlina, Listri (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This research combines various previous research instruments with the aim of obtaining the best results in determining the influence of understanding accounting, accounting information systems and internal control systems on the quality of study financial reports on MSME in the culinary sector in the city of Bandung. Quantitative techniques with descriptive and verification approaches are used to determine the relationship between three independent variables and one dependent variable. The data for this research was separated into two categories: primary data from respondent questionnaires and secondary data from books, papers and other relevant literature. The Slovin formula is used to determine the minimum sample size from a limited population, as well as to avoid sampling errors that may occur. In this case, the sample was selected using a purposive sampling strategy and non-probability sampling techniques. The number of MSME in the culinary sector in 2002 was 335 and in 2023 it was 557 in the city of Bandung, using a purposive sampling strategy and non-probability sampling method. These entrepreneurs have met the criteria for implementing the MSME Accounting Information System (AIS) which is considered representative of the entire population. The research results show that understanding accounting, accounting information systems, and internal control systems greatly influence the quality of financial reports. Therefore, efforts to increase the implementation of SIA for MSME should be concentrated on increasing understanding of accounting and internal control of MSME entrepreneurs regarding the quality of financial reports, especially for MSMEs in the culinary sector.